SÍNTESE, CARACTERIZAÇÃO E TESTES DE ATIVIDADE BIOLÓGICA DE COMPLEXOS DE ÍONS LANTÂNIO E EURÓPIO - ESPEDITO DE SOUSA SARAIVA (2024)
Since the emergence of the concept of coordination compounds in the late 1950s, a large number of studies have been reported in the literature and related research has covered many fields, such as: catalysis, optical fibers, chemical sensors, biomarkers, drug delivery, contrast agents and cancer therapy. In this context, lanthanide(III) ion complexes have been extensively studied since the 19th century due to their spectroscopic and magnetic properties. The field of research into these compounds has grown very rapidly in the last two decades due to their applications in industrial catalysts, diagnostic agents, molecular probes, LEDs, among others. In this work, eight lanthanide ion coordination compounds (La and Eu) were synthesized with the ligands cyclobutane-1,1-dicarboxylic acid (cbdca), 1,10-phenanthroline (phen) and dibenzoylmethane (dbm). These were characterized using the techniques of Fourier Transform Infrared Absorption Spectroscopy (FTIR), 1H Nuclear Magnetic Resonance Spectroscopy (1H NMR) and Thermogravimetric Analysis (TG/DTG). The formation of coordination compounds was evaluated by using FTIR based on the displacement of absorption bands of the free ligands cbdca, dbm and phen, as well as the displacement and broadening of the signals referring to the hydrogens of the ligands cbdca, dbm and phen in the 1H NMR spectra. The minimum inhibitory concentration (MIC) of the La2(cbdca)3⸱(H2O)2 and La2(cbdca)3(phen)⸱(H2O) complexes was determined against Staphylococcus aureus. In vitro antiproliferative activity in MCF7 and U251 tumor cells was performed for organic precursors (ligands) and inorganic precursors (lanthanide salts), as well as for the 8 lanthanide ion complexes.